2021
DOI: 10.3390/educsci11030123
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Educational Factors to Promote Educational Inclusion in Higher Education. A Question of Student Achievement

Abstract: Psychosocial factors have a direct impact on the academic achievement of university students, especially when they belong to diverse human groups. This article shows the results of a project developed in a Colombian university with the aim of finding out the identity traits, situations of discrimination, and risk factors faced by students belonging to diverse groups. The research is qualitative, exploratory, and descriptive, approached from a social and educational perspective. Semi-structured interviews were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…With a significant level of dynamism in the change of factors of external influence, a significant increase in risks and threats, socionomic factors of the formation of professional competencies of future specialists in socionomic professions should be subject to permanent monitoring by researchers. These changes determine the need for constant transformations of methods and tools used in the educational process, which to some extent contradicts the opinion established in the scientific literature [2,3,5] about the sufficiency of the implementation of only one or another set of measures. At the same time, the work of Bonfield et al [11] indicated the need to modify the tools of the educational environment in accordance with threats, but, unfortunately, did not mention the permanent nature of threat assessment, namely, the permanent nature of threat assessment requires, in our opinion, the implementation of constant monitoring and threat assessment by both scientists and HEI administrations.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…With a significant level of dynamism in the change of factors of external influence, a significant increase in risks and threats, socionomic factors of the formation of professional competencies of future specialists in socionomic professions should be subject to permanent monitoring by researchers. These changes determine the need for constant transformations of methods and tools used in the educational process, which to some extent contradicts the opinion established in the scientific literature [2,3,5] about the sufficiency of the implementation of only one or another set of measures. At the same time, the work of Bonfield et al [11] indicated the need to modify the tools of the educational environment in accordance with threats, but, unfortunately, did not mention the permanent nature of threat assessment, namely, the permanent nature of threat assessment requires, in our opinion, the implementation of constant monitoring and threat assessment by both scientists and HEI administrations.…”
Section: Discussionmentioning
confidence: 93%
“…Since, according to estimates [2,9], the budget for creating an educational environment in higher education institutions of developed countries can exceed 400,000 dollars. based on the results of the authors' analysis, we propose a phased introduction to the educational environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another work [28] studied the state of academic awareness surrounding intersexuality in early childhood, primary and secondary education, finding a lack of research and academic ignorance that demonstrates the difficulty in implementing programs and measures for improved diversity and inclusion. Other recent research [29] emphasizes the role of socio-educational factors in the promotion of inclusion in the university environment, as these factors have a significant impact on academic performance in the most marginalized populations.…”
Section: Introductionmentioning
confidence: 99%
“…Diferentes investigaciones y estudios han establecido el marco donde se inscriben las experiencias educativas de segunda oportunidad, a través de diferentes dispositivos que diseñan acciones más flexibles y diversificadas ofreciendo opciones y oportunidades adaptadas para cubrir las competencias clave, basadas en los elementos aparecidos en la Recomendación del Parlamento Europeo y del Consejo, de 18 de diciembre de 2006 relativa a las competencias clave para el aprendizaje permanente (2006/962/CE), y que se completan con formación práctica en centros de trabajo, ofreciendo de este modo una segunda oportunidad educativa (Olmos, 2014;Prieto, 2015;Salva, Nadal & Agnés, 2017;Vázquez & Barrera, 2017;Olmos & Más, 2018;Martíns, Carneiro, Campos, Mota, Negrão, Baptista & Matos, 2020;García, Medina, Amashta & Higueras, 2021).…”
unclassified